The Role of Digital Banking Facilities in Supporting the Mining Industry in Indonesia - Permana, Riko Mersandro (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The mining industry in Indonesia plays an important role in the country's economy. To support this sector's smooth operation and growth, digital banking facilities are increasingly becoming an important element in transaction processes and financial management. This study aims to analyze the role of digital banking facilities in supporting the mining industry, focusing on transaction efficiency, ease of access to funding, and enhanced transparency and security. Based on qualitative research and data collected through literature studies, this article finds that digital banking facilities significantly contribute to modernizing the Indonesian mining industry. The existence of these facilities helps mining companies to expedite payment processes, minimize financial risks, and enhance operational efficiency.